Reliability analysis of reinforced concrete slabs according to NBR 6118 considering the lateral confinement - Gabriel Orso Garcia; Mauro de Vasconcellos Real; Paula Manica Lazzari (Revista IBRACON de Estruturas e Materiais)
Abstract The effect of lateral confinement in reinforced concrete slabs is widely recognized for its ability to increase the supported ultimate load. In this context, this study proposes a reliability analysis of slabs designed according to Brazilian standards, considering or not the phenomenon, with the goal of establishing a comparison between the cases. A numerical model developed in ANSYS software, calibrated from experimental results, was used to determine the slabs' failure loads. The Monte Carlo Simulation Method was employed to obtain the failure probabilities and reliability indexes. Additionally, a parametric study was conducted to understand the main factors influencing the reliability, whether considering lateral confinement or not. The results indicated a significant increase in the reliability of the slabs when lateral confinement was considered, raising the average reliability index from 3.29 to 4.44. The parametric study revealed that the factors influencing the reliability of confined slabs are similar to those obtained when not considering it, as also demonstrated by the strong correlation between the reliability indexes of confined and unconfined slabs.